A reassessment of variation in Kalanchoe gastonis-bonnieri (Crassulaceae subfam. Cotyledonoideae), a pseudo-rosulate species from Madagascar: reinstatement of K. adolphi-engleri at the rank of varietas under K. gastonis-bonnieri - Smith, Gideon F. (Phytotaxa, 2024)
Variation found in the Malagasy Kalanchoe gastonis-bonnieri (Crassulaceae subfam. Cotyledonoideae) is discussed. Kalanchoe adolphi-engleri, previosuly included in the synonymy of K. gastonis-bonnieri, is here reinstated under K. gastonis-bonnieri, at the rank of varietas. Kalanchoe gastonis-bonnieri var. adolphi-engleri is applied to material that is largely devoid of a dense, white-waxy pruinosity; has generally inconspicuous leaf surface maculation; and a corolla tube and corolla lobes that are often nearly uniformly reddish purple.